Delineation of Irrigation Network Performance in Subak in South Denpasar District, Bali Province - Ardana, Putu Doddy Heka; Pamungkas, Tri Hayatining; Agustin, Elin Alviana; Syamsunur, Defrizon (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Massive conversion of agricultural land into built-up land occurred in South Denpasar District. These changes impacted the decline in rice production by 5.5% in 2023 and a decrease in the performance of the irrigation network. This study employs GIS to assess the efficacy of irrigation networks to enhance sustainable agriculture, community food security, and irrigation and subak network systems in South Denpasar. This study used spatial analysis to create an irrigation network performance map. Data analysis interprets primary data based on field observation to assess the irrigation network's physical condition. The irrigation network is divided into four levels: good, slightly damaged, medium damaged, and badly damaged. The study indicated that Subak Sesetan disintegrated since it was thought to have turned into a village. The land conversion reduced the 292.593 Ha of subak (Kerdung, Cuculan, Kepaon, and Sesetan) to 186.314 Ha, or 36.32%. The length of irrigation canals was 16.901 Km, with good conditions along 16.67 Km or 98.61%, slightly damaged conditions along 0.051 Km or 0.3%, and moderately damaged conditions along 0.1842 Km or 1.09%. This research should help South Denpasar District stakeholders decide on land-use change strategies and rehabilitation or irrigation network development priorities.